Implementation of Case Management in Hospitals - I Komang Alit Susilayasa; N L P Dina Susanti; L G Nita Sri Wahyuningsih; I A Putri Wulandari (Jurnal Keperawatan, 2024)
Health services, especially the provision of care to patients in hospitals, are increasingly complex and require an increase in the quality of services that are increasingly well coordinated or known as integrated services. Therefore we need a proper service approach model, namely through case management carried out by case managers (CM) in hospitals. The presence of a CM to carry out case management is very important but requires readiness so that they are able to carry out case management properly. Therefore, a literature study is needed to determine the extent of implementation of case management in hospitals. This literature study uses two databases (Pubmed and ScienceDirect) as well as other sources. In total, there were 283 articles obtained through searching the data based, and there were eight articles that met the requirements (included). The results of the literature study found that the implementation of case management in hospitals still varied. Case management leads to better patient care and increased interpersonal and emotional relationships between patients and healthcare providers in hospitals. In addition, the implementation of case management has an impact on integrated care and better use of health services. Another finding is in the form of an experimental study that provides interventions to improve CM skills in implementing case management.